Links between fringe pattern analysis and digital image correlation : windowed, optimal, and tracking (WOT) - Qian, Kemao (2015)
A windowed, optimal and tracking (WOT) strategy for measurement data analysis is described, explained and discussed. Many fringe pattern analysis and digital image correlation algorithms adopted this strategy, and thus their similarities and links are revealed. Although this strategy is not new, highlighting it is believed to be helpful for future algorithm development.